Pooled clone collections by multiplexed CRISPR-Cas12a-assisted gene tagging in yeast [dataset] - Buchmuller, Benjamin; Herbst, Konrad; Meurer, Matthias; Kirrmaier, Daniel; Sass, Ehud; Levy, Emmanuel D.; Knop, Michael (Universität, 2019)
Data accompanying the paper "Pooled clone collections by multiplexed CRISPR-Cas12a-assisted gene tagging in yeast" by Buchmuller and Herbst et al, 2019, Nat Communications. This contains raw NGS data for all genotyping analysis in the publication as well as the source code of the castR design software (v1.0).
Time period covered: start: 2017 ; end: 2018
Kind of Data: next-generation sequencing analysis
Gesehen am 16.05.2019
Keywords: Forschungsdaten; Datenbank